Plasma brain-derived neurotrophic factor in women with pelvic pain: a potential biomarker for endometriosis?. (April 2017) - Rocha, Ana L; Vieira, Erica L; Ferreira, Márcia C; Maia, Laura M; Teixeira, Antonio L; Reis, Fernando M
Aim: To test whether plasma BDNF levels are useful to predict the presence of endometriosis in women with pelvic pain.Patients & methods: Prospective cross-sectional study including 67 consecutive women aged 24–49 years, scheduled for laparoscopy due to chronic pelvic pain. Preoperative plasma samples were assayed for BDNF using a commercial enzyme immunoassay.Results: Women with ovarian endometrioma had higher preoperative plasma BDNF (1063 ± 157 pg/ml) compared with women with other benign ovarian tumors (537 ± 131 pg/ml, F = 2.53; p = 0.02). However, plasma BDNF levels were not helpful to indicate the presence of peritoneal or deep infiltrating endometriosis. Plasma BDNF levels were positively correlated with the severity of pelvic pain (r = 0.489; p < 0.0001).Conclusion: Plasma BDNF might be a biomarker of ovarian endometrioma but not a useful diagnostic marker to detect other forms of endometriosis in women with painful symptoms.